Adjuncts for sputum clearance in COPD: clinical consensus versus actual use. Issue 1 (29th July 2017) - Barker, Ruth; Laverty, Anthony A; Hopkinson, Nicholas S
Abstract : Introduction: Oscillatory positive pressure devices (OPEP) can be used as adjuncts to improve sputum clearance in chronic obstructive pulmonary disease (COPD), though the evidence base is incomplete. The attitudes of physiotherapists towards these devices in the care of patients with COPD is unknown. In addition, actual use compared with the prescription of medications has not been studied. Methods: We analysed English prescribing data, obtained from OpenPrescribing.net, for a 3-year period from 2013. In addition, we conducted an online survey of members of the Association of Chartered Physiotherapists in Respiratory Care regarding awareness of devices, thresholds for treatment and device preference. Results: Out of a potential 3.2 million COPD patient-years of treatment between 2013 and 2015, 422 744 patient-years of treatment with carbocisteine, at a cost of £73 million, were prescribed, as well as 1.1 million years treatment with tiotropium. In the same period, only 4989 OPEP devices were prescribed. There were 116 responses to the survey (12% response rate), 72% in hospital practice, 28% based in the community. There were variations in respondents' threshold for treatment with sputum adjuncts in COPD, and when asked to select either the Acapella, Flutter or positive expiratory pressure mask, preferences were 69%, 24% or 6%, respectively. Conclusions: There is a 100-fold difference between use of carbocisteine and OPEP devices in COPD, with far fewer devices prescribed than are included in the phenotypes clinicians believe them to be effective in. Variation in physiotherapist attitudes to treatment thresholds highlights the need for research into the effectiveness of OPEP devices in specific patient phenotypes.